Socialization Of Educational Equality/Inclusion Through Coloring Competition Activities For Early Childhood In Medan City - Putri Sari Ulfa Sembiring; Kharida Shaleha (Outline Publisher, 2025)
Community Service through coloring competitions with normal children as participants and ABK aims to provide knowledge to participants regarding inclusive education in formal school for Children with Special Needs. This activity is expected to be a medium for community so that inclusive learning can be provided appropriately. This inclusive education is expected can be a way opener for Indonesian children with special needs to go to school and side by side with normal children without any negative stigma for Children with Needs Special. The activity is carried out by demonstrating how to color and facilitating children children to learn to color. By holding this activity, it is hoped that kindergarten children can improve mindset and self-confidence in early childhood. And to develop creativity and imagination in early childhood. This activity is also expected to increase quality of inclusive education in the city of Medan. The result of this activity is to increase the sense of togetherness and acceptance of ABK towards normal children.